The study about determining the reliability of operations management, risk warning and opportunity of repair risk (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
In this paper, how to transform operations management and supply chain management, industrial engineering problems, project management, and other issues into a complex system reliability problem has been provided. It become possible that reliability of users demand is determined first and opportunity of choosing the repair the risk. This paper can provide a theoretical basis for research on related issues, which has a certain value.